Rostro-Caudal and Caudo-Rostral Migrations in the Telencephalon: Going Forward or Backward? - Ruiz-Reig, Nuria; Studer, Michèle (Frontiers in Neuroscience, 2017)
The generation and differentiation of an appropriate number of neurons, as well as its distribution in different parts of the brain, is crucial for the proper establishment, maintenance and plasticity of neuronal circuitries. Newborn neurons travel along the brain, in a process called neuronal migration, to finalize their correct position in the nervous system. Defects in neuronal migration produce abnormalities in the brain that can generate neurodevelopmental pathologies, such as autism, schizophrenia and intellectual disability. In this review, we present an overview of the developmental origin of the different telencephalic subdivisions and a further description of migratory pathways taken by some neural populations that travel long distances before reaching their target position in the brain. In addition, we will discuss some of the molecules implicated in the guidance of these migratory paths and transcription factors that contribute to the correct migration and integration of these neurons.